FRI0460 Differences and similarities of spondyloarthritis classification subgroups defined by the assessment of spondyloarthritis international society (ASAS). (23rd January 2014) - Paramarta, J.; Van de Schoot, M.; Turina, M.; Ambarus, C.; Bijlsma, J.; De Rycke, L.; Baeten, D.
Abstract : Background: Since the Assessment of SpondyloArthritis international Society (ASAS) developed new classification criteria, spondyloarthritis (SpA) is no longer divided into different phenotypic subtypes such as ankylosing spondylitis and psoriatic arthritis, but into axial and peripheral SpA. Objectives: This study aimed to compare the clinical characteristics and disease activity of the different SpA subpopulations according to the new ASAS criteria. Methods: 389 patients presenting on two dedicated SpA outpatient clinics fulfilling the European Spondyloarthropathy Study Group (ESSG) criteria were included in a prospective observational cohort. Baseline characteristics were collected and patient's and physician's global assessment of disease activity, Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Ankylosing Spondylitis Disease Activity Score (ASDAS), 68 swollen and tender joint count, Schober, ESR and CRP were measured every 3 months. Data were analyzed with Mann Whitney U and chi square tests. Results: 314 of the 389 SpA patients (81%) fulfilled the ASAS classification criteria. Patients fulfilling the ASAS criteria had a younger age at disease onset (median 34.1 vs 38.2), were more often male (61.8 vs 36.0%) and HLA-B27 positive (65.1 vs 2.9%), and had more often sacroiliitis on imaging (53.4 vs 1.4%) than those who did not fulfil the ASAS criteria. Strikingly, most disease activity parameters were similar between the two groups and the median BASDAI (4.6 vs 5.3) and TJC (0 vs 3) was even higher in the latter group. Of the patients fulfilling the ASAS criteria, 230 (59% of the total population) fulfilled the axial and 84 (22%) the peripheral SpA criteria. ASAS peripheral SpA had an older age at disease onset (32.3 vs 38.2) and were less often HLA-B27 positive (76.2 vs 27.3%) than ASAS axial SpA. The parameters of global disease activity (patient's and physician's global assessment and ASDAS) were higher in axial than peripheral SpA, whereas CRP and ESR were similar. As the ASAS criteria exclude patients with active axial symptoms from the peripheral SpA group but do not exclude patients with peripheral disease from the axial SpA group, we additionally subdivided patients who fulfilled the ASAS axial SpA criteria into pure axial and combined disease (back pain plus arthritis, enthesitis or dactylitis). The combined group was intermediate between pure axial SpA and peripheral SpA in terms of clinical characteristics such as disease symptoms and age at disease onset. Most importantly, the combined group had the highest disease activity compared to the other two groups (eg. ASDAS 3.0 vs 2.6 and 2.0, respectively). Conclusions: The ASAS criteria fail to classify a subgroup of 20% of the patients fulfilling the ESSG criteria and having high disease activity. Within the patients fulfilling the ASAS axial SpA criteria, we discriminate two separate groups corresponding to exclusive axial disease versus combined axial and peripheral disease. These data support a classification into axial, combined, or peripheral disease rather than just axial versus peripheral disease. The combined group could enter the classification through either the axial or peripheral SpA criteria. Disclosure of Interest: None Declared